Molecular mechanism of lycopene cyclases regulating carotenoids ratio in different branches during tea leaf and flower development - Anqi Peng; Xiaoyan Tang; Yingying Feng; Yun Huang; Jilai Cui; Kai Tian; Mengqian Lu; Yifan Zhao; Yuting Pan; Sanjin Wang; Yutong Hu; Wei Zhao; et al. (Horticultural Plant Journal, 2023)
Carotenoids are essential components in tea quality, contributing to leaf color and aroma. However, little information about carotenoids in different tea cultivars and their biosynthesis regulation mechanism during leaf development is known. Here we analyzed carotenoids by HPLC in the buds and leaves of 113 tea cultivars harvested on the same day. By profile clustering, carotenoids were divided into five groups. Same group cultivars displayed divergence in the total content of carotenoids but a similar molar ratio. To figure out the molecular mechanisms of this phenomenon, we further characterized all functional lycopene cyclases, which are the branch point of the carotenoid biosynthesis pathway. Two β-lycopene cyclases (CsLCYB1 and CsLCYB2) and one ε-lycopene cyclase (CsLCYE1) were cloned. Subcellular localization analysis showed that all cloned CsLCYs were localized in plastids. Enzyme activity assays in E. coli indicated both CsLCYBs catalyzed lycopene into β-carotene, and CsLCYE1 produced δ-carotene and ε-carotene. We found CsLCYB1 and CsLCYE1 predominantly expressed in leaf, while CsLCYB2 was mainly expressed during flowering stages. Suppression by antisense oligonucleotides reduced CsLCYB1 and CsLCYE1 transcripts and led to reduction of both β,β-branch and β,ε-branch carotenoids in leaf. The expression levels of CsLCYB1 showed a significant positive correlation with β,β-branch carotenoids in leaf. Our study provides carotenoid profiles of different tea cultivars, which can assist tea producers in selecting cultivars of interest. Meanwhile, we proposed the molecular mechanism of carotenoids reflecting the tenderness of tea plant leaf from a metabolic flux perspective, and suggested lycopene cyclase that could be applied to the breeding of tea varieties with different branch carotenoids.